Soil and crop response to phosphorus and potassium management under conservation tillage. (13th March 2020) - Yuan, Mingwei; Fernández, Fabián G.; Pittelkow, Cameron M.; Greer, Kristin D.; Schaefer, Daniel
Abstract: In conservation tillage systems, proper fertilizer phosphorus (P) and potassium (K) management is critical to optimize yield and minimize negative environmental impacts. The objective of this study was to assess the responses of crop yield, nutrient use efficiencies, root growth, and soil test P and K levels to tillage, fertilizer placement, and fertilizer rates in a corn ( Zea mays L.)–soybean [ Glycine max (L.) Merr.] rotation. Experiments were conducted for 8 yr in Illinois with tillage/fertilizer placement as the main plot (no‐till/broadcast [NTBC], strip‐till/broadcast [STBC], and strip‐till/deep band [STDB]) and PK fertilizer rates as the subplot. The NTBC treatment consistently reduced yields in corn by 6.2 and 4.5% and in soybean by 3.1 and 6.1% relative to STBC and STDB, respectively. Also, NTBC had greater root length density at in‐row and between‐row positions relative to STBC and STDB. Nutrient use efficiency indices (partial nutrient balance, agronomic efficiency, and partial factor productivity) declined with increasing P and K rates but were not affected by tillage/fertilizer placement treatments. Deep banding significantly reduced soil P and K concentrations in surface layers while increasing them at the depth of application. These results underscore the reported potential for deep banding combined with strip‐till to improve conditions for nutrient uptake while reducing the risk for nutrient losses to the environment. Critical soil test P and K levels (21 mg P kg −1 and 217 mg K kg −1 ) were similar for P and greater for K than the current university recommendations, which highlights the need for continuous refinement of soil fertility recommendations to keep pace with changes in production technologies and yield levels.